The Characterization of J-Integral for Elastic-Plastic Crack Growth Evaluation using Finite Element Analysis - Heng, S H; Muhamad Azmi, M S; Rojan, M A; Hashim, M S M; Ismail, A H (International Journal of Integrated Engineering, 2021)
J-integral is a fracture mechanic parameter that can be used to characterize elastic-plastic fracture mechanic (EPFM) behavior. The path independent characteristic in J-integral is proposed by Rice [1], and it is widely used in a lot of research. Another approach is the load-displacement approach, where the J-integral is calculated by the area under the load-displacement curve. However, the validity of the J-integral value by load-displacement approach is yet to be confirmed. This paper is aimed to investigate the effect of crack length ratio of CT specimen to J-integral value by two approaches: path-integral approach and load-displacement approach. Finite element analysis of compact tension (CT) model with crack length ratio a/W between 0.2 to 0.5 was carried out under displacement Î´ between 0.2 to 1.0 mm using ANSYS parametric design language (APDL). The J value by path integral approach, Jpath is compared to the value calculated from load-displacement approach, Jp-d. It was found that path independency occurs for J value evaluated from path integral approach. A correction factor needs to be introduced since the load-displacement approach cannot be used for shallow crack cases.